Síntese e caracterização do compósito de LiFePO4/Pani para aplicação em baterias de íons lítio - Fagundes, Wélique Silva (2015)
This work aims at the synthesis of the LiFePO4 by solvotermal method and the study of the influence of the synthesis temperature on the structure and morphology of the LiFePO4. In addition, the composite LiFePO4/PAni was prepared by chemical synthesis to promote the intensification of the electrochemical properties for use as cathodes in lithium ion batteries. The X-ray diffraction (XRD) of LiFePO4 synthesized at different temperatures (170-200 °C), regardless of the temperature employed, presented more intense and defined diffraction peaks, which were indexed to the orthorhombic structure. Cyclic voltammograms of LiFePO4 synthesized at temperatures below 180 °C showed no electroactivity. The cyclic voltammogram of LiFePO4 synthesized at 200 oC presented the most well-defined redox and its XRD showed the greater intensification of the ratio of the diffraction peaks 211/111 (1.210), indicating a better planning of the LiFePO4 particles. The cyclic voltammogram of the composite synthesized chemically showed a profile predominantly faradaic, a good redox reversibility (Ep = 0.20) and low charge transfer resistance values (14 Ω cm2). However, the composite prepared via physical mixture showed a predominantly capacitive and resistive profile, which prevents their application as cathode in secondary batteries. Thus, only the LiFePO4 / polyaniline composite chemically synthesized was selected for the charge and discharge tests. The galvanostatic tests showed that the specific capacity value obtained for the LiFePO4/polyaniline was 149 mA h g-1 at C/7 and a coulombic efficiency of 97 % after 20 cycles, indicating a good electrochemical stability. So the solvotermal synthesis of the LiFePO4, as well as the synthesis of the composite LiFePO4/PAni are efficient approaches to circumvent the problem of low electronic and ionic conductivity of the LiFePO4.